Relationship among B1-EPG, VPT and EPT Graphs Classes - Alcón, Liliana Graciela (2023)
This research contains as a main result the proof that every chordal B1-EPG graph is simultaneously in the graph classes VPT and EPT. In addition, we describe structures that must be present in any B1-EPG graph which does not admit a Helly-B1-EPG representation. In particular, this paper presents some features of non-trivial families of graphs properly contained in Helly-B1-EPG, namely bipartite, block, cactus and line graphs of bipartite graphs.